RESPONSE OF COTTON TO NITROGEN FERTILIZER AND SPACING BETWEEN HOLES - & et al., Alubaidi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This experiment was conducted at the farm of field crop department, College of Agriculture, University of Baghdad during two summer seasons (2010 and 2011) in order to know the response of cotton var. Lashata to nitrogen levels and spacing between holes. A randomized complete block design under arrangement of split plot with four replications was used. The plant spacing; 10, 20 and 30 cm between holes and 75 cm between rows considered as main plots, while three nitrogen levels (150, 200 and 250 Kg N.ha-1) are considered as sub plots. The results showed that using 10 cm between hills were significantly superior in boll weight (3.69 and 4.26) gm.boll-1, seed cotton yield (3.03 and 3.6) t.ha-1 and lint yield (1.13 and 1.30) t.ha-1 in both seasons 2010 and 2011 respectively. While, 30 cm spacing significantly superior in number of open bolls (12.10 and 13.6) bolls.plant-1 and ginning percentage (39.05 and 37.44)% in both seasons respectively. The nitrogen fertilizer 250 kg N ha-1 was significantly superior in dehiscence bolls number, seed cotton yield, lint yield and ginning percentage in both seasons 2010 and 2011 respectively. It can be concluded that 'using 10 cm spacing between holes with 250 kg N ha-1 to achieve highest seed cotton yield.